1977
DOI: 10.1139/y77-107
|View full text |Cite
|
Sign up to set email alerts
|

Proximal–distal absorptive gradients in the in vivo intestine of normal and infected (Hymenolepis diminuta: Cestoda) rats

Abstract: Using a single-pass perfusion technique, H2O, Na+, Cl-, HCO3-, and glucose absorption were studied in the jejunum and proximal and distal ileum of rats either uninfected or infected with a tapeworm parasite (Hymenolepis diminuta). The effect of parasitization, region of the intestine, type of buffer, and concentration of glucose in the perfusion fluids on the transport data were analyzed by univariate and multivariate techniques. Proximal-distal flux gradients were observed for water and all the solute species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Rivier (1973) reported that although riboflavin uptake was related to the presence of Na+, it was the flux of water following the actively transported Na+ which was responsible for riboflavin uptake. The increased riboflavin uptake per unit water flux in parasitized animals is in agreement with the hypothesis that the worms had not affected the active transport component of riboflavin transport whereas they had decreased Na+ and water transport (Podesta and Mettrick, 1977) resulting in inhibition of the passive component of riboflavin uptake.…”
Section: Discussionsupporting
confidence: 88%
“…Rivier (1973) reported that although riboflavin uptake was related to the presence of Na+, it was the flux of water following the actively transported Na+ which was responsible for riboflavin uptake. The increased riboflavin uptake per unit water flux in parasitized animals is in agreement with the hypothesis that the worms had not affected the active transport component of riboflavin transport whereas they had decreased Na+ and water transport (Podesta and Mettrick, 1977) resulting in inhibition of the passive component of riboflavin uptake.…”
Section: Discussionsupporting
confidence: 88%
“…After 32 days since invasion, mastocytosis, or increased number of mast cells, was observed in mucous membrane of intestine, as well as hypertrophy of smooth muscle layer (Dwinell et al, 1994;1997;1998). These changes were HELMINTHOLOGIA, 49, 4: 233 -240, 2012 Changes of enzymatic antioxidant system in the small intestine of rats after the chronic invasion by Hymenolepis diminuta (Cestoda, Hymenolepididae) noted in all parts of alimentary tract, which is connected with relatively large dimensions of the parasite and its migration through the intestine in circadian cycle, in response to food ingestion by the host (Podesta & Mettrick, 1977). In spite of that, invaded rats live long and tapeworms, in the case of invasions not leading to overpopulation, remain in the intestines of the rat until its death, what may prove mutual adaptation in the setting parasite-host.…”
Section: Introductionmentioning
confidence: 99%